2011
DOI: 10.4028/www.scientific.net/amr.243-249.2389
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Pile-Base Post-Grouting Effects of Piles of Liao River Bridge

Abstract: Static load tests were carried out with Osterberg method on 3 bored piles formed in Liao River Bridge. Bearing capacity, base resistance and frictional resistance were obtained before and after base grouting. Based on the test results, the ultimate bearing capacities of piles were increased for 14.74%~43.87%, that of pile bases were increased for 89.57% ~ 163.49% and the frictional resistances were most increased for 31.20%. The pile bearing behavior was improved. Not only base resistances were improved after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…With this method, pressure signals from the rotating system are collected and fed back to the controller, and then the force of the feeding system is controlled. Post-grouting is a new technique that improves the stability of a bored-pile foundation [29], which has been successfully applied in the Jamuna Bridge over the Brahmaputra River in Bangladesh. Both the side and tip of the cast-in situ piles were post-grouted, improving skin friction and tip resistance [30].…”
Section: Cast-in Situ Bored Pilesmentioning
confidence: 99%
See 1 more Smart Citation
“…With this method, pressure signals from the rotating system are collected and fed back to the controller, and then the force of the feeding system is controlled. Post-grouting is a new technique that improves the stability of a bored-pile foundation [29], which has been successfully applied in the Jamuna Bridge over the Brahmaputra River in Bangladesh. Both the side and tip of the cast-in situ piles were post-grouted, improving skin friction and tip resistance [30].…”
Section: Cast-in Situ Bored Pilesmentioning
confidence: 99%
“…In addition to improvements in process technology, the constructors may prioritize construction quality while constructing bored piles, e.g., the end bearing resistance, the speed of footage, slurry quality, and pouring concrete velocity [25]. Hence, when dealing with loose and easily slumping soil layers, it is advisable to bury the casing appropriately deep and seal it with clay to prevent issues such as pile collapse [29]. Udomchai et al (2018) [9] have found that a long and stiff bored pile can improve the external stability of the structure by increasing the embedment length to obtain high passive lateral resistance.…”
Section: Cast-in Situ Bored Pilesmentioning
confidence: 99%